Keeping up with the ageing Joneses - Walter H. Fisher; Ben J. Heijdra (Institute for Advanced Studies (IHS), 2007)
In this paper we consider the implications of relative consumption externalities in the Blanchard-Yaari overlapping generations framework. Unlike most of the macroeconomic literature that studies this question, the differences between agents, and, thus, in their relative position, persist in equilibrium. We show in our fixed employment model that consumption externalities lower consumption and the capital stock in long-run equilibrium, a result in sharp contrast to the recent findings of Liu and Turnovsky (2005). In addition, we solve for the intertemporal path of the economy to investigate its response to demographic shocks, specifically, to permanent changes in the birth and death rates.
Keywords: D91; E21; 330; relative consumption; overlapping generations; demographic shocks; Konsumentenverhalten; Konsuminterdependenz; Bevölkerungsentwicklung; Schock; Overlapping Generations; Theorie